SPATIAL PATTERNS OF TELECOMMUNICATION SIGNAL QUALITY, INTERNET SPEED, AND ONLINE GAME LATENCY IN EAST JAKARTA - Septian, M Rizky; Susilowati, Maria H.D.; Zulkarnain, Faris (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2021)
In urban areas where there are many centers of government, trade, education, and other activity, telecommunication device is widely used on publication, transactions or services, administration and promotion, while the internet needs of individuals are commonly used for communication, socialization, seeking information and entertainment. At this time, online games are not only played by using a personal computer but also the presence of a smartphone with its advanced technology that can be connected with the internet network is one of device for online gaming. Mobile gaming requires good latency to run smoothly and comfortably. The need for the telecommunications system uses frequency waves for signal propagation. However, signal propagation can be interrupted due to many factors that affect, for example, distance from BTS (Base Transceiver Station), building density, and terrain shape. This study investigated the relationship between signal quality, internet speed, and latency to the distance from BTS, building density, and shape of the terrain. The results showed that signal quality, internet speed, and good latency were found in areas where near BTS and had a low level of building density.